Aspects of carbon dioxide mitigation by Nannochloropsis oculata cultured in a photobioreactor - Krishnan, V. (Trans Tech Publications Ltd, 2014)
This paper primarily presents on carbon dioxide mitigation by marine microalgae. Among the potential marine microalgae, Nannochloropsis oculata has been identified as a promising species which can be utilized to reduce carbon dioxide concentration via photosynthesis process. The growth of N. oculata and lipid synthesis for biodiesel production is influenced by various aspects. The aspects that are focused in this paper include light source and intensity, temperature, carbon dioxide concentration, and photobioreactor design. Besides, emerging technologies that are able to increase the efficiency of carbon dioxide reduction were also highlighted. As a whole, N. oculata might play a key role in reducing the global carbon dioxide emission as well as enhancing the biodiesel production. Â© 2014 Trans Tech Publications, Switzerland.